Extending Catalyst Life in Glycerol-to-Acrolein Conversion Using Non-thermal Plasma - Liu, Lu; Ye, Xiaofei Philip; Katryniok, Benjamin; Capron, Mickaël; Paul, Sébastien; Dumeignil, Franck (Frontiers in Chemistry, 2019)
Booming biodiesel production worldwide demands valorization of its byproduct of glycerol. Acrolein, an important intermediate chemical, can be produced by gas-phase glycerol dehydration catalyzed by solid acids. Because catalysts that lead to high acrolein selectivity usually deactivate rapidly due to the formation of coke that blocks the active sites on their surface, one major challenge of this method is how to extend the service life of the catalyst. Silica-supported silicotungstic acid (HSiW-Si) is a good example of such a catalyst that shows good activity in glycerol dehydration to acrolein initially, but deactivates quickly. In this study, HSiW-Si was selected to probe the potential of using nonthermal plasma with oxygen-containing gas as the discharge gas (NTP-O2) to solve the catalyst deactivation problem. NTP-O2 was found to be effective in coke removal and catalyst regeneration at low temperatures without damaging the Keggin structure of the HSiW-Si catalyst.